Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 9 - Review: 9



Work Step by Step

We are given that $f(x)=x^{2}-2$, $g(x)=x+1$, and $h(x)=x^{3}-x^{2}$. We know that $(f\circ g)(x)=f(g(x))$. Therefore, $(f\circ g)(-1)=f(g(-1))=f(-1+1)=f(0)=0^{2}-2=-2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.